Tourism Suitability and Carrying Capacity as a Basis for Sustainable Coastal Ecotourism Development at Karangsong Beach, Indonesia - Muhammad Haerizal Arrafi; Ambariyanto Ambariyanto; Ita Widowati; Agus Indarjo (Jurnal Kelautan Tropis, 2026)
Coastal ecotourism development requires an integrated understanding of environmental suitability, ecological carrying capacity, and management strategies to ensure long-term sustainability. This study evaluates the suitability of tourism, carrying capacity, and development strategies for sustainable coastal ecotourism at Karangsong Beach, Indramayu Regency, Indonesia. Tourism suitability and carrying capacity were assessed based on biophysical parameters, field observations, and stakeholder surveys. Tourism suitability was analyzed using the Tourism Suitability Index (TSI), while the Area Carrying Capacity (ACC) was calculated to determine the maximum number of visitors that can be accommodated without compromising environmental quality or visitor comfort. Strategic priorities for ecotourism development were identified using an integrated SWOT analysis and Quantitative Strategic Planning Matrix (QSPM). The results indicate spatial variation in tourism suitability across the study area, with several coastal segments classified as highly suitable for tourism activities, while others require management interventions. The carrying capacity analysis suggests that Karangsong Beach can sustainably accommodate an average of 184 visitors per day under current environmental conditions. Priority development strategies include improving and maintaining tourism facilities, enhancing accessibility, strengthening community participation in tourism management, and conserving mangrove ecosystems as key ecotourism attractions. This study demonstrates that integrating tourism suitability assessment and carrying capacity analysis provides a robust scientific framework for sustainable coastal ecotourism planning. The findings offer practical insights for balancing tourism development, coastal ecosystem conservation, and community-based economic benefits and contribute to sustainable marine ecotourism management in tropical coastal regions.